A Review on Transdermal Drug Delivery System - Rohini U, Sante; Fugate , Ajay; Yelkote , Priyanka D; Phulari, Madhuri M; Patil , Sneha R; Ritthe, Punam V; Shaikh I, Imran (Asian Journal of Pharmaceutical Research and Development, 2024)
Transdermal patches are designed to deliver drugs across the skin membrane without causing pain. This method of drug delivery, known as transdermal delivery, was first used in 1981 when Ciba-Geigy smarketed Transdermal V (now marketed as Transderm Scop) to prevent nausea and vomiting associated with motion sickness. Transdermal patches are pharmaceutical preparations of varying sizes, containing one or more active ingredients, which are applied to unbroken skin to deliver the active ingredient after passing through the skin barriers, thus avoiding first-pass metabolism. Today, about 74% of drugs are taken orally and often prove ineffective. To improve drug efficacy, transdermal drug delivery systems have emerged. The main objective of these systems is to deliver drugs into systemic circulation through the skin at a predetermined rate with minimal inter- and intra-patient variations.